2020
DOI: 10.3390/ijms21072455
|View full text |Cite
|
Sign up to set email alerts
|

Shape Anisotropic Iron Oxide-Based Magnetic Nanoparticles: Synthesis and Biomedical Applications

Abstract: Research on iron oxide-based magnetic nanoparticles and their clinical use has been, so far, mainly focused on the spherical shape. However, efforts have been made to develop synthetic routes that produce different anisotropic shapes not only in magnetite nanoparticles, but also in other ferrites, as their magnetic behavior and biological activity can be improved by controlling the shape. Ferrite nanoparticles show several properties that arise from finite-size and surface effects, like high magnetization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 194 publications
(211 reference statements)
1
72
0
Order By: Relevance
“…Moreover, the sigmoidal shape of the loop is characteristic of nanostructures with small magnetic fields [65]. The weak magnetism could be due to the presence of a higher amount of Fe 2 O 3 phase which is also evidenced by the XRD [66].…”
Section: Vibrating Sample Magnetometer (Vsm) (Magnetization Study)mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the sigmoidal shape of the loop is characteristic of nanostructures with small magnetic fields [65]. The weak magnetism could be due to the presence of a higher amount of Fe 2 O 3 phase which is also evidenced by the XRD [66].…”
Section: Vibrating Sample Magnetometer (Vsm) (Magnetization Study)mentioning
confidence: 81%
“…The disappearance of hysteresis with a little remanence and coercivity (Hc), indicates the absence as a long-range magnetic dipole-dipole interaction among the assemblies of superparamagnetic nanoparticles [64]. Moreover, the sigmoidal shape of the loop is characteristic of nanostructures with small magnetic fields [65]. The weak magnetism could be due to the presence of a higher amount of Fe2O3 phase which is also evidenced by the XRD [66].…”
Section: Vibrating Sample Magnetometer (Vsm) (Magnetization Study)mentioning
confidence: 88%
“…High magnetization and hysteretic heating make them potential candidates in separation and biomedical areas, and the semiconducting property and chemically active surface allow catalytic activities such as photocatalytic ability [ 8 , 9 ]. Iron oxide nanoparticles (IONPs) have a broad range of significant applications in electronics [ 10 , 11 ], biomedicine [ 12 , 13 , 14 ], energy [ 15 , 16 ], agriculture [ 17 , 18 ], and animal biotechnology [ 19 , 20 ], as shown in Figure 1 . In a small size of about 10–20 nm, the superparamagnetic properties of Fe 3 O 4 and γ-Fe 2 O 3 nanoparticles become apparent, therefore, better performance can be achieved for the above-mentioned applications.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro evaluation on iron oxide nanorods and nanospheres carried out in human carcinoma cells indicated that hematite nanorods were more quickly and in a higher extend internalized than nanospheres [13]. The more favorable cellular uptake of rod-shaped NPs, as opposed to spherical NPs, Andrade et al [14], explained with the larger area of contact between the cell membrane and rod-shaped NP. Comparing tripod with spherical iron oxide NPs, it has been found that tripod particles had lower cytotoxicity in HeLa and Hepa 1-6 cells at concentrations between 0.022 and 0.35 mg Fe/mL [15].…”
Section: Shape and Sizementioning
confidence: 99%